Is local authority procurement supporting SMEs? An analysis of practice in English local authorities. Issue 3 (3rd May 2016) - Loader, Kim
ABSTRACT: The UK coalition government wishes to improve the access of small- and medium-sized enterprises (SMEs) to public procurement, in recognition of their importance to the economy and for the benefits they can bring to public procurement and the wider public sector. Local government provides a significant opportunity for small firms, spending £84 billion of the total procurement spend of £230 billion. However, about two-thirds of both small businesses and local authorities think that SMEs face barriers in successfully accessing public procurement. This paper examines how councils are supporting SMEs in the procurement process by analysing 67 entry forms to the 'Best Councils to do business with' competition. This unique data source has provided insight into councils' attitudes and procurement practices, and demonstrates that although a wide range of supportive actions are being employed there is considerable diversity across councils. Ambiguities and tensions in policies, between local and central government, have also emerged.